The need for first aid education for adolescents - Mohd Sharif, Nur Amirah; Che Hasan, Muhammad Kamil; Che Jamaludin, Farrah Ilyani; Firdaus, Mohd Khairul Zul Hasymi (Elsevier, 2017)
Objective: The objective of this study is to identify the need for basic first aid knowledge and skills among adolescents. Method: A cross-sectional study using multistage sampling was conducted among 375 secondary school students in Kuantan, Pahang, Malaysia. The survey was adapted from a Hong Kong Red Cross survey. A back to back translation of this instrument was carried out by two bilingual medical experts with Cronbach’s alpha 0.8. The data were analyzed using SPSS (Statistical Package for the Social Sciences) in terms of descriptive analysis, and an independent t-test and chisquare test were carried out. Results: There were 149 respondents from the lower form (grade level) and 226 respondents from the upper form. The majority of respondents (81.6%) were Malay. An independent t-test revealed a significant association between knowledge and attitude, as students who scored higher on first aid questions showed a more positive attitude towards first aid (1.475%). There were also significant associations between race and experience learning first aid. Conclusions: Adolescents receive minimal first aid education. Thus, there is an urgent need to educate adolescents more in first aid to promote a safer community and to prevent any further injuries.